2019
DOI: 10.15288/jsad.2019.80.366
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Recreational and Spiritual Peyote Use Among American Indian Youth

Abstract: Some American Indians legally use hallucinogenic substances as part of religious and spiritual ceremonies. Research to date has either failed to differentiate spiritual versus recreational use or has categorized hallucinogen use in an "other drug" or "illegal drug" category. This approach could contribute to ineffectual models of prevention and treatment intervention and limit understanding of hallucinogen use in American Indian cultures. Method: This study is a secondary data analysis of an ongoing epidemiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Another possible explanation for why mescaline use in our study was associated with decreased SUD while LSD and psilocybin use were not, could be that mescaline is typically used in a more supportive context than LSD or psilocybin (26,51). While the influence of set and setting was not accounted for in this study due to survey limitations, set and setting could have contributed to the different SUD outcomes seen in the LSD or psilocybin users vs. mescaline users in this study.…”
Section: Directions For Future Researchmentioning
confidence: 69%
See 1 more Smart Citation
“…Another possible explanation for why mescaline use in our study was associated with decreased SUD while LSD and psilocybin use were not, could be that mescaline is typically used in a more supportive context than LSD or psilocybin (26,51). While the influence of set and setting was not accounted for in this study due to survey limitations, set and setting could have contributed to the different SUD outcomes seen in the LSD or psilocybin users vs. mescaline users in this study.…”
Section: Directions For Future Researchmentioning
confidence: 69%
“…It is for this reason that researchers believe that many indigenous groups have participated in sacramental ritual use of psychedelics for religious and pedagogical purposes since ancient times ( 11 , 23 ). Examples of such sacramental use include religious consumption of ayahuasca ( 12 , 23 ) and the religious sacrament performed by the Native American Church (NAC) in which peyote is consumed as part of an all-night communal prayer and song ceremony for the purpose of healing physical or spiritual imbalances that an individual or the community may be experiencing ( 15 , 24 26 ). Similarly, ibogaine is often used in ceremonial contexts and in clinical research for addiction treatment ( 27 , 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on the effect of mescaline on alcohol consumption is very scarce and provides conflicting results. Thereby, Prince et al published an epidemiological paper 56 in 2019 exploring the relationship between 30‐day alcohol consumption and peyote use by young American Indians ( n = 3.861). Contrary to what historical reports suggest, the results showed that alcohol consumption was positively associated with peyote use.…”
Section: Resultsmentioning
confidence: 99%
“…Peyote is a small cactus that contains psychoactive properties and mescaline is the primary active compound found within peyote; both peyote and the derivative isolate mescaline are primarily used by indigenous North Americans. There are only few historical studies (Albaugh and Anderson, 1974; Bergman, 1971; Blum et al, 1977) and modern studies (Halpern et al, 2005; Prince et al, 2019) exploring peyote and mescaline use and psychological outcomes within Native American populations and even fewer that that explore the potentially salutary effects of these specific compounds in the population more broadly (Agin-Liebes et al, 2021; Uthaug et al, 2021). Future research that explores whether peyote and mescaline confer lowered odds of other adverse outcomes would fill critical gaps in our knowledge about these compounds.…”
Section: Discussionmentioning
confidence: 99%